2019
DOI: 10.1121/1.5127737
|View full text |Cite
|
Sign up to set email alerts
|

Broadband sound propagation in a seagrass meadow throughout a diurnal cycle

Abstract: Short-range propagation characteristics of airgun pulses during marine seismic reflection surveys

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Finally, a strong diurnal pattern was observed, where detection probability was increasing during the day and declining at night. This is in concordance with findings in previous studies [14,19,27] and has been suggested to be caused by biological sources, such as macrophyte metabolism or animals that are nocturnally active and create background noise. Macrophytes produce oxygen via photosynthesis that is either emitted during day or stored at night [14] thus contributing to the attenuation of the acoustic signal.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, a strong diurnal pattern was observed, where detection probability was increasing during the day and declining at night. This is in concordance with findings in previous studies [14,19,27] and has been suggested to be caused by biological sources, such as macrophyte metabolism or animals that are nocturnally active and create background noise. Macrophytes produce oxygen via photosynthesis that is either emitted during day or stored at night [14] thus contributing to the attenuation of the acoustic signal.…”
Section: Discussionsupporting
confidence: 93%
“…This is in concordance with findings in previous studies [14,19,27] and has been suggested to be caused by biological sources, such as macrophyte metabolism or animals that are nocturnally active and create background noise. Macrophytes produce oxygen via photosynthesis that is either emitted during day or stored at night [14] thus contributing to the attenuation of the acoustic signal. In the Rysstad Basin, the strong diurnal pattern in detection probability is most likely caused by the metabolism of the dense J. bulbosus stands and, therefore, not to be confused for fish behaviour as it may look like fish are hiding during the day but it is actually a loss of range.…”
Section: Discussionsupporting
confidence: 93%
“…Seagrass meadows contain a suite of unique conditions that pose challenges for the performance of acoustic telemetry. Most notably, the oxygen produced in photosynthesis by the plants and either stored in aerenchyma or emitted as bubbles can attenuate acoustic signals and alter sound wave velocity, thereby affecting VPS performance and error [34,35]. Furthermore, many fish species are known to regularly position themselves within the seagrass canopy to rest, shelter from predators or stalk prey [36].…”
Section: Introductionmentioning
confidence: 99%